Three‐dimensional multiscale finite element models for in‐service performance assessment of bridges. (22nd November 2018) - Mashayekhi, Maryam; Santini‐Bell, Erin
Abstract: Accurate representation of the structural performance of civil engineering structures, specifically complex bridge structures, may be achieved through an efficient multiscale finite element (FE) model. Multiscale FE modeling couples multiple dimensions of elements in a single model. In this study, the selected existing multipoint constraint equations applied in planar coupling conditions are modified and refined for out‐of‐plane coupling conditions in a single three‐dimensional FE model. Also, the optimum location for the interface points of different elements is determined to improve the model's accuracy and efficiency. The present case study, the Memorial Bridge in Portsmouth, NH, is a vertical lift bridge, which includes novel gusset‐less connections. These connections have complex geometries and therefore require finer dimension elements to represent the structural behavior, while the remainder of the structure is modeled with coarser dimension elements. To achieve an accurate and efficient multiscale model of the Memorial Bridge, multiple global FE models are developed and the predicted structural responses are verified with respect to the field‐collected structural responses of the bridge.